GENTIANA ARUNII SP. NOV.: TINY REMARKABLE GENTIANA FROM SIKKIM HIMALAYA. (1st December 2017) - Maity, D.; Dey, S. K.; Ghosh, J.; Midday, M.
Abstract : A new species, Gentiana arunii D.Maity, S.K.Dey, J.Ghosh & Midday, from alpine pasture in Sikkim Himalaya is described and illustrated, and placed in Gentiana section Chondrophyllae Bunge. The new species is compared morphologically with two related taxa, Gentiana glabriuscula T.N.Ho and Gentiana pluviarum W.W.Sm. subsp. subtilis (Harry Sm.) T.N.Ho.